RORα fine-tunes the circadian control of hepatic triglyceride synthesis and gluconeogenesis - Chloé Monnier; Munkhzul Ganbold; Martine Auclair; Natacha Roblot; Andréas Barnabé Boutin; Paul Ketil Boutin; Bruno Fève; Bénédicte Antoine (Scientific Reports)
Abstract Circadian rhythms play a fundamental role in hepatic metabolism, orchestrating lipid synthesis and glucose homeostasis. RORα, a nuclear receptor involved in circadian regulation, has been implicated in fine-tuning these metabolic processes. We previously showed a therapeutic potential of antagonizing RORα to reduce body fat in mice. Our current aim is to investigate the impact of the whole-body RORα deletion on hepatic lipid metabolism over a complete circadian cycle. Using RORα-knockout (staggerer) mice, this study reveals a time-dependent disruption in hepatic triglyceride synthesis, with reduced lipogenesis during the light-phase and altered transcriptional regulation of key metabolic genes, including Srebp1c and Insigs. Despite increased Srebp1c transcription at night, the anticipated rise in lipid synthesis was prevented by phase-shifted Insig expression, modulating precursor maturation. Moreover, core clock genes rhythmic expression was attenuated and phase-shifted for Reverbα. Pharmacological inhibition of RORα using an inverse agonist (SR3335) mirrored the metabolic effects observed in staggerer mice, further supporting the role of RORα as a crucial regulator of lipid and glucose homeostasis in mice fed a chow diet. These findings highlight the intricate interaction between the circadian clock and hepatic metabolism, situating RORα as a promising target to prevent metabolic disorders such as obesity and dyslipidemia.